Phenomenology and Agathology - Wesołowska, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The aim of this article is to prove the thesis that relation between phenomenology and agathology – as presented in Józef Tischner’s work – is essential to his philosophy. Two assumptions are discussed here in order to prove main point. First, that by beginning from Husserlian concept of transcendental ‘I’ and grounding his thought in phenomenological analysis, Tischner develops his idea of axiological and agathological ‘I’. Second, Tischner’s concept of ‘dramatic entity’ can be understood as a result of his reflection on Husserlians approach to subjectivity. As it is shown, acceptation of phenomenological point of departure doesn’t cause – for Tischer who follows Husserl – to fall into a dogmatism, but, in contrary, to reveal axiologically-agathological perspective.